Analisis stakeholders pengelolaan kawasan hutan dengan tujuan khusus (KHDTK) mengkendek, Kabupaten Tana Toraja, Provinsi Sulawesi Selatan - Abd. Kadir Wakka (Jurnal Penelitian Kehutanan Wallacea, 2014)
Forest for special purpose of Mengkendek (KHDTK Mengekendek) which directly adjacent to settlement is vulnerable to encroachment, illegal logging, illegal grazing, and forest fires. Requiring the involvement of stakeholders in helping to overcome the existing problems so that the objectives of KHDTK Mengkendek can be realized. This study aims to identify, mapping and formulate the role of stakeholders in the management KHDTK Mengkendek. The data was collected through interviews and focus group discussions then analyzed in descriptive qualitative. The results showed that there are six stakheholders in the management KHDTK Mengkendek. Forestry Research Institute of Makassar, Forestry Office of Tana Toraja, government village/lembang, and traditional institutions (tongkonan) are key players in the management KHDTK Mengkendek. Communication and coordination with the stakeholders must be done well so that the objectives of KHDTK Mengkendek management can be realized.